Applied Hepatic Bioengineering: Modeling the Human Liver Using Organoid and Liver-on-a-Chip Technologies - Telles-Silva, Kayque Alves; Pacheco, Lara; Komatsu, Sabrina; Chianca, Fernanda; Caires-Júnior, Luiz Carlos; Araujo, Bruno Henrique Silva; Goulart, Ernesto; Zatz, Mayana (Frontiers in Bioengineering and Biotechnology, 2022)
The liver is the most important metabolic hub of endo and xenobiotic compounds. Pre-clinical studies using rodents to evaluate the toxicity of new drugs and cosmetics may produce inconclusive results for predicting clinical outcomes in humans, moreover being banned in the European Union. Human liver modeling using primary hepatocytes presents low reproducibility due to batch-to-batch variability, while iPSC-derived hepatocytes in monolayer cultures (2D) show reduced cellular functionality. Here we review the current status of the two most robust in vitro approaches in improving hepatocyte phenotype and metabolism while mimicking the hepatic physiological microenvironment: organoids and liver-on-chip. Both technologies are reviewed in design and manufacturing techniques, following cellular composition and functionality. Furthermore, drug screening and liver diseases modeling efficiencies are summarized. Finally, organoid and liver-on-chip technologies are compared regarding advantages and limitations, aiming to guide the selection of appropriate models for translational research and the development of such technologies.